Women with Abnormal Endometrial Pathology: Experienced at a Tertiary Care Hospital in Bangladesh - Showkat, Mst Syeeda; Khondker, Lubna; Nabi, Shahryar; Bhowmik, Bishwajit (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Transvaginal sonography is superior to transabdominal sonography in most cases of pelvic pathology. Objective: This study was undertaken to see the clinicalpathological characteristics of endometrial hyperplasia. Methodology: This cross sectional study was carried out from January 2007 to December 2008 for a period of two years. All suspected cases of endometrial hyperplasia were included for this study. Transvaginal sonography (TVS) performed and confirmation was done by histopathological examination. Result: A total number of 40 cases were enrolled for this study. The most common diagnosed endometrial pathology was endometrial hyperplasia which was 42.5% cases. Endometrial polyp was diagnosed in 32.5% cases. Endometrial carcinoma was in 7.5% patients and submucosal fibroid was in 10.0%. Conclusion: Endometrial hyperplasia is the most common disease among the women presented with endometrial pathology. DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16198 J Shaheed Suhrawardy Med Coll, 2013;5(1):11-13